The Protagonist’s Inner Beauty Concepts Reflected in Danielle Steel’s Novel Big Girl - Sari Siregar, Nurmaliana; Heridayani, Heridayani; Ani, Fitri; Siregar, Prima Yanti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aimed to explore the concepts of inner beauty reflected in the protagonist of Big Girl, a novel by Danielle Steel. The main character, Victoria Dawson, was portrayed as an intelligent, loyal, and optimistic woman who often faced rejection from her parents due to her physical appearance. This research used a qualitative approach with descriptive analysis based on selected excerpts from the novel. The findings showed that Victoria’s true beauty was expressed through her persistence in pursuing education, her loyalty in relationships, and her optimism in achieving her dream of becoming a teacher. This study emphasized that inner beauty was more meaningful than physical appearance, and Victoria’s character served as a strong representation of moral values and the strength of women in overcoming social and familial pressures.